Developments in gastrointestinal organoid cultures to recapitulate tissue environments - Kuhn, Madeline R.; Wolcott, Emma A.; Langer, Ellen M. (Frontiers in Bioengineering and Biotechnology, 2025)
Culture platforms that closely mimic the spatial architecture, cellular diversity, and extracellular matrix composition of native tissues can serve as invaluable tools for a range of scientific discovery and biomedical applications. Organoids have emerged as a promising alternative to both traditional 2D cell culture and animal models, offering a physiologically relevant 3D culture system for studying human cell biology. Organoids provide a manipulable platform to investigate organ development and function as well as to model patient-specific phenotypes. This mini review examines various methods used for culturing organoids to model normal and disease conditions in gastrointestinal tissues. We focus on how the matrix composition and media formulations can impact cell signaling, altering the baseline cellular phenotypes as well as response to perturbations. We discuss future directions for optimizing organoid culture conditions to improve basic and translational potential.